(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
This study focuses on approaches to mitigating the negative consequences of over-exposure to social media, otherwise identified as detoxification. The theoretical basis of this study includes the social media dependence and reverse domestication theories. The dependence theory explains how individuals could get addicted in their attempts to make the most of the benefits of social media. On the other hand, reverse domestication describes how individuals can mitigate the challenges of overexposure to social media. The population of this survey study is the students in the Department of Mass Communication, Bingham University, Nigeria. Questionnaires were administered to one hundred and forty-two (142) students to obtain the primary data using the non-probabilistic survey method. Study findings validate the emerging trend and inherent dangers of overreliance on social media and approaches to detoxification, such as media fasting, deliberate cutbacks on social media use and the associated emotions. Recommendations include the need for the government to formulate a policy framework and guidelines on the minimum age of exposure to social media and the need for individuals to take responsibility for understanding the value of information on social media before committing time and materials to its consumption.